Symptoms of depression and anxiety and stress among postgraduate trainees in Sri Lanka: Risk factors and implications for practice - Prasangika S. Alles; Luckshika Amarakoon; Yasodha M. Rohanachandra (Indian Journal of Psychiatry)
High workload, long working hours, and the need to study and work simultaneously put postgraduate trainee doctors at a high risk of depression, anxiety, and stress. A cross-sectional descriptive study was conducted among all postgraduate trainees registered at the Postgraduate Institute of Medicine (PGIM), Sri Lanka, using the 21-item Depression Anxiety Stress Scale (DASS-21). Eleven-point two percent (11.2%) had depressive symptoms, 8.9% had anxiety symptoms, and 1.9% had high levels of stress. Being female, having a past or current mental illness, not being supported by the trainers, being unfairly treated by trainers, dissatisfaction with the work environment, difficulty in coping with long working hours, and poor peer support were significantly associated with symptoms of depression and anxiety, and stress (P < 0.01). Given the association between psychological distress and the characteristics of training and work environment, the postgraduate training programs should be reviewed to ensure the psychological well-being of trainees.